Employment After Retirement: A Review and Framework for Future Research. (January 2019) - Sullivan, Sherry E.; Al Ariss, Akram
Retirement was once considered an exit from full-time work into full-time leisure. Research evidence indicates, however, that a growing number of retirees are reentering the labor force. Although a number of reviews have been conducted on retirement, there has been no comprehensive review of the increasing number of studies on work after retirement. It is time to take stock of the accumulated knowledge on postretirement employment that has been produced by scholars across multiple fields. Using the construct of employability as an organizing framework, this review examines postretirement employment in light of the five key dimensions of employability: career motivation, human capital, social capital, identity, and personality. On the basis of this review, we identify trends and gaps in the literature and recommend major directions for future research on postretirement employment.